Mediation Role of Work Stress on the Effect of Work-Life Balance and Work Environ-ment on Employee Performance of XYZ Leasing Company - Tinjung Desy Nursanti; Monica Julianti (Indonesia Banking School, 2021)
The purpose of this study was to determine the effect of work life balance and work environment on work stress and its impact on the performance of XYZ leasing company’s employees. The research method used in this research is associative research method which aims to find out the relationship between two or more variables. Data collection was carried out by distributing questionnaires to 124 respondents and analyzed using the path analysis method. The results of this study are the variable work life balance and work envi-ronment affect work stress and have an impact on the performance of employees of XYZ leasing company. The conclusion from the results of this study is the variable work life balance and work environment sig-nificantly and negatively affect work stress then significantly and positively affect performance. Some practical implications that might be useful for XYZ leasing company are as follows, the company needs to take a look at the ability of employees to balance work demands with personal activities that have become routine, hence the company needs to realize that the process of digitizing work is the answer to the issue of work life balance. Moreover, the company must also try to contribute or improve work support facilities so that the work environment becomes more comfortable, as well as providing more sufficient work equip-ment. With the various improvements made, it is hoped that employees can have punctuality in finishing off their work.